Parametric and nonparametric event study tests : a review - Dutta, Anupam (Canadian Center of Science and Education (CCSE), 2014)
This paper presents a modest attempt to review the existing methodologies for measuring short-run abnormal performance of firms following certain corporate events. In doing so, the study discusses different parametric as well as nonparametric testing procedures available in the literature. Reviewing the prior literature reveals that the nonparametric sign and rank tests are better specified than parametric procedures. However, in case of detecting the short-run anomalies, we document that nonparametric tests have higher power relative to standard parametric approaches.
Keywords: event study; short-run anomalies; sign test; rank test; statistical methods; shares; prices; security market; water analysis; qualification; laboratory research; laboratories; reliability (general); evaluation; Tilastotiede